Producción de leche fermentada utilizando bacterias probióticas (Lactobacillus acidophilus, Bifidobacterium lactís y Streptococcus thermophilus) con leche de cabra y de vaca - Guerrero Alva, Daniza Mirtha (2006)
In the present study was added a culture (composed by Lactobacillus acidophilus, Bifidobacterium lactis and Streptococcus thermophilus) to goat and cow milk and a mix of goat and cow milk (1:1). It was gotten whole fermented milk with good acidity, fat percentage, and enough probiotic bacteria's growth (Lactobacillus acidophilus 107cfu/ml, Bifidobacterium lactis 106cfu/ml), besides Streptococcus thermophilus 109cfu/ml. All of the fennented milks agreed with the food safety norms. The parameters of the process were: added culture (1% in goat and in cow and goat mix milk, fermentation temperature 42°C; 2% in cow milk and fermentation temperature 39°C); final pH of 4,5. The time of process with cow, goat, and cow and goat rnix milk was: 4 hours, 7 hours and 4 hours respectively.